Retrograde Abdominal Hysterectomy - Hiramatsu, Yuji (The Surgery Journal, 2019)
The basic procedure of abdominal hysterectomy is extrafascial hysterectomy, and intrafascial hysterectomy (Aldridge operation) and retrograde hysterectomy are performed as applied surgical procedures. The Aldridge operation and retrograde hysterectomy are performed when strong adhesion is present around the uterus. Retrograde hysterectomy is also useful when the cervicovaginal junction is not clearly felt by palpation, such as when uterine rupture immediately occurs after vaginal delivery or when a large tumor mass is present in the vagina.
Keywords: retrograde hysterectomy; adhesion; large tumor mass in the vagina; uterine rupture